The Kantian Publicity Principle and the Transparency Presumption in Public Affairs: When Private Citizens' Participation Becomes Public Knowledge. (2nd October 2017) - Clinger, James
Abstract : This article applies Immanuel Kant's "publicity principle" to several issues that involve citizen participation in public affairs, including open records laws, campaign finance disclosure, and the confidentiality of private organization membership and donor lists. The Kantian principle is premised on the belief that informed people will rise up in opposition to actions incompatible with "the transcendental concept of public right." However, in many controversies, publicity may serve to threaten—rather than protect—segments of the citizenry who support causes that are not popular with other portions of the populace. The article concludes that the publicity principle applies reasonably well to actions of public officials, but is a less useful guide when applied to the participatory acts of private individuals.